Polymorphism of CSF1 PO, TH01 and TPOX in random Bajau Population of Malaysia - Minsun, Lelyan Minsun (Universiti Sains Malaysia, 2006)
Genotype polymorphism studies at three short tandems repeat (STR) loci (CSF1 PO, TPOX, TH01) were carried out in one ethnic (Bajau) living in Sabah, Malaysia. The analysis was performed on 150 unrelated healthy individuals belonging to Bajau races. The allele frequency of each locus was calculated from the observed number of each genotype. All loci were in accordance with HardyWeinberg equilibrium (P = 0.05). No deviations from equilibrium were observed. The discriminatory power and exclusion probability values for all the analyzed markers are significantly high and thus reveal high forensic significance. Statistical analysis was also carried out to obtain some parameters of medico-legal interest and comparative studies were carried out with other populations studied to date for these loci. This allele frequency data will be useful for forensic analyses and paternity analysis to estimate the frequency of a multiple STR locus DNA profile in Bajau population.